PRELIMINARY PHYTOCHEMICAL ANALYSIS OF THE METHANOL EXTRACT OF RHODODENDRON RENSCHIANUM FLOWERS, ENDEMIC TO KELIMUTU NATIONAL PARK, INDONESIA, USING UV–VIS SPECTROPHOTOMETRY - Damiana Nofita Birhi; Faustina De Yesu Prisila Abi; Antonia Fransiska Laka; Ni Putu Vidya Primarista (Department of Chemistry Faculty of Science and Technology UIN Walisongo, 2026)
Rhododendron renschianum is an endemic Indonesian species characterized by bell-shaped flowers with bright red petals and a yellowish base. This study aimed to document the presence of and quantify major phytochemical groups in the methanolic extract of R. renschianum flowers. Phytochemical screening yielded positive results for triterpenoids, tannins, flavonoids, alkaloids, and quinones. However, quantitative analysis using UV–Vis spectrophotometry indicated an apparent triterpenoid content of 2685.48 ± 123.49 mg UA/g, highlighting a limitation of UV–Vis analysis for investigating reactive compounds such as triterpenoids. The remaining compounds, in ascending order of content, were flavonoids, alkaloids, tannins, and quinones, with values of 5.98 ± 0.70 mg QE/g, 90.09 ± 67.09 mg CAF/g, 109.24 ± 1.44 mg TA/g, and 130.93 ± 30.19 mg HQ/g, respectively. These findings add to the baseline data for the initial investigation of the secondary metabolite content of this endemic species and provide a preliminary basis for further pharmacological research.